2020
DOI: 10.2478/bjreecm-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Road Infrastructure Budgetary Expenditures and Commercial Property Investment Returns. Case Study of Fadikpe Area Minna, Nigeria

Abstract: The paper examines the relationship existing between commercial property investment returns and public capital investment (budgetary expenditures) on road infrastructure in Fadikpe area, Minna (Nigeria) with the aim of determining the degree of impact of public capital investment on commercial property investment returns. The paper addresses a pertinent policy and practice question on the impact of government’s budgetary expenditures on real estate sector of the economy. Government increasingly faces funding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Another study indicates that governments should consider more funding road transportation infrastructure through its budgetary allocation. Additionally, decisions should be considered related to quantifying designed alternative source of funding (property tax) that can be harnessed via capturing the increase in property investment returns (Yakubu, Adeyemi, Sule, & Ogunbajo, 2020). Studies show that developing economies invest less on schools than on roads, both in relative and absolute terms, as a fraction of GDP (Atolia, Li, Marto, & Melina, 2017) A study from (Nyasha & Odhiambo, 2019) stated that is a greater chance that the impact of government spending can lead to the growth of the real sector, especially when expenditure is on growth-enhancing activities such as domestic public investment that crowds-in private investment -such as targeted economic infrastructure development study showed that national competitiveness is influenced basically by the level of institutional development and other seven factors, including infrastructure, in turn, infrastructure factor is determined mainly by the quality of roads, railroad infrastructure, air transport and electricity supply (Palei, 2015) The latter is mainly determined by electricity supply, roads quality, railroad infrastructure, and air transport.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study indicates that governments should consider more funding road transportation infrastructure through its budgetary allocation. Additionally, decisions should be considered related to quantifying designed alternative source of funding (property tax) that can be harnessed via capturing the increase in property investment returns (Yakubu, Adeyemi, Sule, & Ogunbajo, 2020). Studies show that developing economies invest less on schools than on roads, both in relative and absolute terms, as a fraction of GDP (Atolia, Li, Marto, & Melina, 2017) A study from (Nyasha & Odhiambo, 2019) stated that is a greater chance that the impact of government spending can lead to the growth of the real sector, especially when expenditure is on growth-enhancing activities such as domestic public investment that crowds-in private investment -such as targeted economic infrastructure development study showed that national competitiveness is influenced basically by the level of institutional development and other seven factors, including infrastructure, in turn, infrastructure factor is determined mainly by the quality of roads, railroad infrastructure, air transport and electricity supply (Palei, 2015) The latter is mainly determined by electricity supply, roads quality, railroad infrastructure, and air transport.…”
Section: Literature Reviewmentioning
confidence: 99%